The Effect of Snail Mucus (Achatina fulica) on Wound Healing after Tooth Extraction: A Literature Review - Ridho, Fiki Muhammad; Pamungkas, Adhe Retnantya; Faisal, Ahmad (Penerbit Goodwood, 2023)
Purpose: Tooth extraction is a frequently performed procedure within the field of dentistry, which results in a wound. The wound healing process can be enhanced by chemical and traditional medicines, one of which is snail mucus, which contains active compounds that play an important role in wound healing process. This study aims to further discuss regarding the effect of snail mucus on wound healing process after tooth extraction. Methodology/approach: This literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through PubMed, ProQuest, and Google Scholar database. Results/findings: Snail mucus contains active compounds, such as protein, glycosaminoglycans, metal elements, allantoin, sulfates, calcium, mytimacin-AF, collagen, elastin, glycolic acid, hyaluronic acid, glutathione and vitamins which have effectiveness in enhancing the wound healing process with different mechanisms for each compound, both hemostasis, inflammation, proliferation, and remodeling processes. Limitation: The limitation of this literature review is the lack of high-quality research. Furthermore, the lack of information on the specific doses of snail mucus used and the duration of treatment are critical difficulties that should be addressed in future research to allow for more comprehensive meta-analysis. Additionally, it is required to conduct testing and comparative analysis of the composition of snail mucus across other species in order to ascertain the efficacy of snail mucus content in species other than Achatina fulica. Contribution: The results of this literature review are expected to be a reference in scientific development of wound treatment using traditional medicine, particularly snail mucus. Additionally, it is expected to increase the understanding regarding the effect of snail mucus on wound healing after tooth extraction.